Allergia agli animali di laboratorio: follow-up in un istituto di ricerca / Laboratory animal allergy: follow-up in a research centre - Cauz, Paola; Bovenzi, Massimo; Larese Filon, Francesca (La Medicina del Lavoro, 2014)
Summary «Laboratory animal allergy: follow-up in a research centre». Background: Laboratory animal allergy (LAA) is frequent in exposed workers despite working conditions and exposure to these allergens having improved over the last decade. The aim of this study was to assess LAA in students and workers in a research facility within the framework of a prevention programme. Subjects and methods: Students and researchers working with laboratory animals underwent medical surveillance every year from 2001 to 2012. They filled in a standardized questionnaire for the assessment of allergic respiratory symptoms and exposure conditions. Skin prick tests with common allergens, latex and hair extract from laboratory animals were performed at the first control and after three years of exposure. Results: 198 women and 120 men with a mean age of 29.1±7.3 years and a work seniority of 3.1±6.5 years participated in the study. Sensitization to laboratory animals ranged between 11.8 and 14.8% according to work seniority. Sixteen subjects (5%) reported asthma and 25 (7.9%) rhinitis when working with laboratory animals. LAA was associated with the female gender (OR 3.1; IC 95% 2.3-5.8), with atopy by prick test (OR 7.0; IC 95% 2.9-16.9), and with sensitization to laboratory animals (OR 2.7; IC 95% 1.1-6.7). Conclusion: This study revealed a low level of sensitization and symptoms of allergy to laboratory animals as a result of the preventive measures adopted to reduce exposure, but there is nonetheless a need to improve prevention so as to completely avoid the onset of LAA in students and workers. Riassunto Background: L’allergia ad animali di laboratorio è tuttora un rilievo frequente nonostante il miglioramento delle condizioni lavorative. Obiettivo del nostro studio è stato quello di valutare sensibilizzazione e sintomi allergici nei soggetti esposti a tali animali in un laboratorio di ricerca. Materiali e metodi: Dal 2001 al 2012 i soggetti esposti ad animali di laboratorio sono stati sottoposti a visita prima dell’inizio della mansione e poi annualmente. Tutti hanno compilato un questionario standardizzato per la valutazione della sintomatologia allergica e sono stati sottoposti a prick test. I lavoratori che prestavano attività in modo continuativo sono stati sottoposti a nuovi test allergometrici dopo 3 anni dal primo accertamento. Risultati: Il gruppo era costituito da 198 donne e 120 uomini, con età media di 29,1± 7,3 anni e una durata di esposizione ad animali di laboratorio pari a 3,1± 6,5 anni. La sensibilizzazione agli animali di laboratorio era presente nell’11,8-14,8% dei soggetti. Asma e rinite da animali di laboratorio era presente in 16 (5%) e in 25 soggetti (7,9%) rispettivamente. I sintomi allergici sul lavoro sono risultati associati al sesso femminile (OR 3,1; IC 95% 2,3-5,8), all’atopia per gli allergeni comuni (OR 7,0; IC 95% 2,9-16,9) e alla sensibilizzazione agli animali di laboratorio (OR 2,7; IC 95% 1,1-6,7). Conclusioni: Il nostro studio ha rilevato una basso livello di sensibilizzazione e sintomi da animali di laboratorio, come risultato delle misure preventive adottate per ridurre l’esposizione. Sono tuttavia necessari ulteriori interventi per evitare completamente lo sviluppo dell’allergia agli animali di laboratorio.